The massive star population of the Virgo Cluster galaxy NGC 4535 - Spetsieri, Z. T.; Bonanos, A. Z.; Kourniotis, M.; Yang, M.; Lianou, S.; Bellas-Velidis, I.; Gavras, P.; Hatzidimitriou, D.; Kopsacheili, M.; Moretti, M. I.; Nota, A.; Pouliasis, E.; et al. (arXiv e-prints, 2018)
We analyzed the massive star population of the Virgo Cluster galaxy NGC 4535 using archival Hubble Space Telescope Wide Field Planetary Camera 2 images in filters F555W and F814W, equivalent to Johnson V and Kron-Cousins I. We performed high precision point spread function fitting photometry of 24353 sources including 3762 candidate blue supergiants, 841 candidate yellow supergiants and 370 candidate red supergiants. We estimated the ratio of blue to red supergiants as a decreasing function of galactocentric radius. Using Modules for Experiments in Stellar Astrophysics isochrones at solar metallicity, we defined the luminosity function and estimated the star formation history of the galaxy over the last 60 Myrs. We conducted a variability search in the V and I filters using three variability indexes: the median absolute deviation, the interquartile range and the inverse von-Neumann ratio. This analysis yielded 120 new variable candidates with absolute magnitudes ranging from M$_{V}$ = $-$4 to $-$11 mag. We used the MESA evolutionary tracks at solar metallicity, to classify the variables based on their absolute magnitude and their position on the color-magnitude diagram. Among the new candidate variable sources are eight candidate variable red supergiants, three candidate variable yellow supergiants and one candidate luminous blue variable, which we suggest for follow-up observations.
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Solar and Stellar Astrophysics